Correlation between composition and radiation shielding performance in neodymium-doped barium borate glasses (Kuwait Journal of Science)
This work focuses on evaluating four glasses' radiation shielding ability, with compositions of (18+2x)BaO–17PbO2-(65-3x)B2O3-xNd2O3 (where x = 0, 1, 2, and 3 mol%), using Phy-X at Eu-152 source-emitted energies. The glasses are designated as Ba18Nd0, Ba20Nd1, Ba22Nd2, and Ba24Nd3, each representing specific concentrations of components BaO and Nd2O3. Glass sample Ba18Nd0's gamma radiation transmission factor (TF) is studied at different thicknesses of 0.25, 0.75, and 1.25 cm, and the results show the TF to be close to zero at very low energy, thus indicating the lower energy photons to be almost completely absorbed by the glass sample. With a 0.25–1.25 cm glass thickness increase, the TF decreases, suggesting the glasses' improved radiation shielding ability. The radiation protection efficiency (RPE) was determined and found to have a positive relation with the glasses' density. In terms of the sample with higher BaO and Nd2O3 content (i.e., Ba24Nd3), there is a higher mean free path than for the other prepared glasses. The glasses' half-value layer (HVL) at 0.122 MeV is 0.10 cm, while with increased energy the HVL decreases to 0.725–1.14 cm at 0.296 MeV and 1.18–1.08 cm at 0.411 MeV. © 2025 The Authors